Diagnosis and management of adnexal masses - Prajapati, Riddhi Rakeshkumar; Shah, Akshay C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Adnexal masses are a commonly encountered gynecological problem. Appropriate evaluation to discriminate between benign and malignant masses helps to guide gynecologists for proper evaluation and management. This study aimed to determine the prevalence of different histopathologic types of adnexal masses among women presenting to our hospital. We also aimed to describe known risk factors of epithelial ovarian cancer and compare the preoperative evaluation and histopathologic diagnosis of adnexal masses. Aims and objectives were to study the clinical nature of adnexal mass, to study different sites and pathology of adnexal masses, to study radio logical and histopathological nature of adnexal mass managed surgically, to determine clinical, radio logical, and histopathological co-relation of adnexal mass. Methods: This was prospective, observational study of patients having ‘adnexal masses’, conducted from May 2023 to December 2023 at our tertiary care hospital. Clinical diagnosis was confirmed by ultrasonography and histopathology. Results: Adnexal masses are more common in nulliparous and common associated risk factors are PID and genital TB. The commonest symptom on patients with adnexal masses was abdominal pain. In present study, most common histopathological diagnosis was ruptured ectopic pregnancy. Conclusions: Adnexal masses are common gynecological problem mostly found in reproductive age group women and in them they were mostly non neoplastic and benign, whereas in peri and post-menopausal age group were malignant. Ectopic pregnancy is the most common presentation of adnexal masses in reproductive age group. Laparoscopic approach is most preferred approach for adnexal masses removal.